Determinants of Work Life Balance among Female Employee in Public and Private Sector Enterprises: Exploring the Impact of Work Life Balance on Female Employees in Public and Private Sectors (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With this expanding industrialization and education, employment open doors for ladies have likewise expanded. Just when an employer has a positive Work Life Balance (WLB), can be profitable and give the best to association. Thus businesses are working out plans which can pull in just as hold their employees. Because of expanding economic conditions, it has turned into a need that both husband and spouse need to work to have a typical life. In this quickly developing and focused world, as each conceivable open door for employment is expanded, the associations need to make an amicable atmosphere where employees can balance their expert and personal life. Today, work is broadly seen as a wellspring of personal fulfillment. A decent balance in work and life can assume an exceptional job in the achievement of personal and expert objectives. Work-life 'imbalance' has over some stretch of time pulled in concern due to expanding issues identified with employee health, monotony at workplace, declining levels of profitability and proficiency at the employee level. We see that there is a changing role of Women in the Society. There are working in many organizations, some have become Entrepreneurs and stuff. In this Research we are try to find out the main motive of Work Life Balance and its impact on Women working Public and Private sectors and their determinants.